Effects of UV-C Light Exposure and Refrigeration on Phenolic and Antioxidant Profiles of Subtropical Fruits (Litchi, Longan, and Rambutan) in Different Fruit Forms - Peilong Li; Xiaoming Yu; Baojun Xu (Journal of Food Quality)
The objectives of this study were to investigate how UV-C irradiation and refrigeration affect shelf-life and antioxidant level of litchi, longan, and rambutan. Three forms (whole, dehulled, and destoned) of fresh fruits were treated by refrigeration and UV-C irradiations. After processing, deterioration rate, phenolics compounds, and antioxidant capacity were quantified. The deterioration rate was recorded as decay index. The results showed that both refrigeration and UV-C exposure extended the shelf-life of the fruits. The refrigeration enriched antioxidant levels of litchi but caused nutritional degradation in longan and rambutan; UV-C radiation enriched litchi antioxidant contents but was related to reduction of antioxidant capacity in longan and rambutan. Removing hulls and stones was associated with the decrease of antioxidants in litchi. The effects on antioxidant levels varied from fruit to fruit, resulting from hormesis phenomenon. The change of phytochemical levels was hypothesized as an accumulative process. The effects of fruit forms were not consistent in different fruits, which could be multifactorially influenced.